2014
DOI: 10.1002/pip.2462
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent down‐shifting experiment and modelling with multiple photovoltaic technologies

Abstract: Luminescent down shifting (LDS) is a viable way for improving the short‐wavelength response of many photovoltaic technologies, such as cadmium telluride, copper‐indium‐gallium‐(di)selenide and multi‐crystalline silicon solar cells. In this work, we compare the experimental performance of LDS layers fabricated with six organic dyes—both alone and in mixtures—and two polymers with the theoretical predictions obtained by three different approaches: ray‐tracing simulations and two novel theoretical models. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…The nontechnical aspect of aesthetics is becoming increasingly important with the advent of novel and niche applications and markets for the PV industry, such as that of building-integrated PV (BIPV), where a broader range of presentational options is desirable [2]- [4]. The authors have shown in previous work that the inclusion of luminescent materials in the design of a PV module can increase the short-wavelength (λ) response and thus efficiency (η) of most in-production PV technologies [5]- [11]. The luminescent species must be hosted in a layer above the solar cells so that favorable spectral shaping can be achieved by means of luminescent down-shifting (LDS) of the ultraviolet (UV) and blue photons contained in the incident spectrum to longer visible λ, where solar cells respond much more efficiently.…”
Section: Integration Of Color and Graphical Design For Photovoltaic Mmentioning
confidence: 99%
“…The nontechnical aspect of aesthetics is becoming increasingly important with the advent of novel and niche applications and markets for the PV industry, such as that of building-integrated PV (BIPV), where a broader range of presentational options is desirable [2]- [4]. The authors have shown in previous work that the inclusion of luminescent materials in the design of a PV module can increase the short-wavelength (λ) response and thus efficiency (η) of most in-production PV technologies [5]- [11]. The luminescent species must be hosted in a layer above the solar cells so that favorable spectral shaping can be achieved by means of luminescent down-shifting (LDS) of the ultraviolet (UV) and blue photons contained in the incident spectrum to longer visible λ, where solar cells respond much more efficiently.…”
Section: Integration Of Color and Graphical Design For Photovoltaic Mmentioning
confidence: 99%
“…Luminescent quantum dots (QDs), organic and organometallic luminescent complexes have been considered for the application 10,11 . In this contribution we studied phosphors as one more candidate for successful LDS 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] As one of the excellent host materials for Ln 3+ activators, LaF 3 has characteristics such as low vibrational energy (about 350 cm −1 ), 9 high thermal stability, and environmental stability. 10 However, Ln 3+ doped LaF 3 also possesses an intrinsic limit, which is their low optical absorption coefficient.…”
Section: Introductionmentioning
confidence: 99%